Measuring the Low-Income Earner on Housing Access in Urban Areas of Indonesia and Malaysia - Mazliza Mohamad; Ricco Survival Yubaidi; Safinaz Mohd Hussein; Rahmah Ismail; Suzanna Mohamed Isa; Saidatul Nadia Abdul Aziz (Faculty of Law, Hasanuddin University, 2021)
The ratio between the increased demand and limited land makes affordable housing in urban areas more difficult to accommodate. Indonesia and Malaysia, as populous countries, face problems related to housing access, especially for low-income earners in urban areas. The research was undertaken for two reasons. First, problems related to housing access for low-income earners in urban areas should be solved as soon as possible. Second, it is necessary to conduct a study in order to analyze and compare these two countries in measuring low-income earners on housing access in urban areas. To this end, the normative legal approach was applied. The materials used in this study were relevant statutes, rules, regulations, journals, articles, thesis, seminar papers, and electronic materials. The result showed that the fulfillment of housing access highly depends on the state’s developmental goals. It is also associated with principles of development that each country adheres to. The government is expected to provide accurate data in measuring low-income earners on housing access. Identification of beneficiaries by combining income classification and ability to housing access may facilitate policymakers with ease when taking affirmative measures. It is necessary to suggest initiative collaboration involving academicians, business sectors, community, and government (ABCG) in Indonesia and Malaysia to provide adequate housing in urban areas.